UK clinicians' views on the use of formulations for the management of BPSD: a multidisciplinary survey. (2nd December 2021) - James, Ian A.; Mahesh, Mithila; Duffy, Frances; Reichelt, Katharina; Moniz-Cook, Esme
Abstract: Background and objectives: The process of formulating in the area of dementia care is at an early stage of development. A review published in 2016, identified 14 different types of formulation-based approaches for the management of Behavioural and Psychological Symptoms of Dementia (BPSD). The present study examines professionals' views about the use of systematic formulations for choosing first-line non-pharmacological interventions for BPSD. Methods: A 34-item online survey, with six items about formulation-based interventions for the management of BPSD, was circulated to multi-disciplinary UK dementia networks. Quantitative data were examined for the use of formulation-based frameworks in practice. Thematic analyses provided insight into the practicalities of using formulations. Results: The majority of the 355 participants responding to the questions stated they used formulation-led models to inform interventions, but 24% stated they did not. Thirty-two types of formulation frameworks were named, and there was a diverse spread across the UK. The Newcastle model was the most frequently used framework, with fifty percent of the participants who formulated reporting using this framework. Four themes regarding the use of formulation emerged, relating to function, process, reported outcomes and obstacles. Conclusion: Formulation-based approaches to targeting intervention are becoming popular in dementia care in the UK. More types of formulation frameworks are used in practice compared with the 2016 review. The use of formulations are seen as key to offering an alternative to pharmacological treatments. Understanding both the value of formulation-led approaches and the obstacles to their use are important to implementing NICE 2018 recommendations.